2020
DOI: 10.30574/gjeta.2020.5.1.0073
|View full text |Cite
|
Sign up to set email alerts
|

Design a solar power air conditioning system for the engineering building at Mutah University

Abstract: Jordan like the other non-oil countries, spend significant amount of its budget on importing foreign energy. Also, the power demand increases due to, the population growth, in addition to hosting high number of refugees, from neighboring countries, and the enhancement of the citizen life style. The objective of this study, is to define the cooling load requirement, for the engineering building, at Mutah University, in order to analyze suitable cooling system, to cater the required cooling load. Energy analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
(6 reference statements)
1
1
0
Order By: Relevance
“…The results of this study are consistent with the findings of Farajat et al [16]. The comparative analysis results indicated that the cooling load required equalled 560 kW, while the electrical energy needed to power the cooling system equalled 224 kW.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study are consistent with the findings of Farajat et al [16]. The comparative analysis results indicated that the cooling load required equalled 560 kW, while the electrical energy needed to power the cooling system equalled 224 kW.…”
Section: Resultssupporting
confidence: 92%
“…However, when the weather is cloudy and no sufficient solar radiation exists, their efficiency in cooling can remarkably decline. Farajat et al [16] carried out research to investigate the key role of solar PV system in providing cooling, depended on a comparative analysis. They compare the economic feasibility of two options to provide cooling.…”
Section: Introductionmentioning
confidence: 99%